Osama and The Entry of Al Qaeda to Southeast Asia in Historical Perspective: A Preliminary Note - Herdi Sahrasad; Yanuardi Syukur; Al Chaidar; Dedy Tabrany; Muhammad Ridwan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Southeast Asia captivates Al Qaeda (Saudi Arabia/Middle East)  to enter this region because Osama Bin Laden knows that Southeast Asia is the second priority of the US in fighting international terrorism. Southeast Asia is also referred to as "home" for terrorist groups or movements such as Jemaah Islamiah (JI), Abu Sayyaf and the Mujahideen Malaysia Group (KKM)) which were allegedly involved in the WTC case. Regardless of whether or not the involvement of "radical Islamic" groups was involved with ‘’the September 11(9/11)’’ case, which clearly has changed US relations with Southeast Asian countries. Meanwhile, the Islamic political movement, especially the  political violence groups have increased and flourished in Indonesia since President Soeharto fell in 1998.  Since the mid-1990s, a number of terrorist attacks have been planned in the Southeast Asia region, including attacks on church leaders (Pope), President Bill Clinton, and commercial aircraft. But these plans are not  always successful, and all of the above factors, combined with the arrest of several people from the Al-Qaeda network operating in Southeast Asia, are seen as a strong enough driving factor to carry out the terrorism attacks in this region. Al Qaeda succeeded in building networks, supporters and cells through regional extremist movements affiliated with it. According to Asean  intelligent report, they received financial and weapons amounted to US$ hundred thousands from Al Qaeda on a scale that worried many people.